1996
DOI: 10.17986/blm.199613148
|View full text |Cite
|
Sign up to set email alerts
|

Yaş Cinsiyet ve Eğitime Bağlı Yazı ve İmza Değişiklikleri

Abstract: Yaşlılık yazının en fazla değişime uğradığı dönemdir. Bu çalışmada yaşa bağlı yazı ve imza değişikliklerinin özelliklerini ortaya koyabilmek amacıyla yaşlı ve genç olguların rastlantısal seçimi ile oluşturulan gruplar karşılaştırmalı olarak incelendi. Yazı ve imza özellikleri incelenirken dikey hat, yatay hat, sol boşluk, sağ boşluk, yazı boyutu, yazı hızı, harfler arası mesafe, okunaklılık, imla uyumu, kopyalamada hata, imza boyutu, imza tutarlılığı, ilk imza-son imza uyumu parametreleri kullanılmaktadır. Yaş… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Various factors affect the changes in handwriting and signature, some may be revealed immediately but some remain unresolved even after great effort and a considerable amount of work (19). In particular, files sent with the request of document examination belonging to elderly people should include a medical report indicating the writer's health status, medical history, information of drug usage and the existence of any disease that may change the handwriting.…”
Section: Discussionmentioning
confidence: 99%
“…Various factors affect the changes in handwriting and signature, some may be revealed immediately but some remain unresolved even after great effort and a considerable amount of work (19). In particular, files sent with the request of document examination belonging to elderly people should include a medical report indicating the writer's health status, medical history, information of drug usage and the existence of any disease that may change the handwriting.…”
Section: Discussionmentioning
confidence: 99%
“…After these studies were conducted, signature science has been taken for examination in Turkey as well based on law. Alkan (1996) has one of the important studies conducted in the field of forensic sciences. Alkan (1996) conducted a study in order to identify whether the individuals' signatures change when they get old, and he compared the data obtained in terms of various writing parameters.…”
Section: Signature Educationmentioning
confidence: 99%
“…Alkan (1996) has one of the important studies conducted in the field of forensic sciences. Alkan (1996) conducted a study in order to identify whether the individuals' signatures change when they get old, and he compared the data obtained in terms of various writing parameters. As a result of the study, it has been identified that the changes can be observed on signatures depending on aging (Alkan, 1996).…”
Section: Signature Educationmentioning
confidence: 99%
See 1 more Smart Citation